The Position of Legal Protection for Debtors for Bankruptcy Conducted by Separatist Creditors in terms of Act No. 4 of 1996 concerning Mortgage Rights - Retno Sulistyowati (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The purpose of this research is to know and analyze; 1). The current implementation of debtor legal protection for bankruptcy is carried out by separatist creditors. 2) Factors that influence the implementation of debtor's legal protection for bankruptcy carried out by separatist creditors. 3) The proper implementation of debtor legal protection for bankruptcy by separatist creditors. This study uses a normative juridical research method, using a statutory approach and a conceptual approach. This type of research is descriptive analytical. The data collection technique is the literature study of this thesis. The data analysis method is descriptive qualitative analytical. The results show that: 1. The implementation of the Bankruptcy Law has not provided protection to debtors, because: The requirements for requesting a bankruptcy statement make it easier for the debtor to be declared bankrupt, even though the debtor is actually in a solvent condition; The PKPU mechanism has not provided broad opportunities for debtors to improve company performance; and Efforts in bankruptcy are dominated by the authority of creditors. 2. Factors that influence the implementation of debtor's legal protection against bankruptcy carried out by separative creditors are: There are no funds for the costs of managing and settling bankruptcy assets; Bankrupt Debtor is not cooperative; and The debtor sells/transfers his assets before being declared bankrupt. 3. The Bankruptcy Law in future requires an insolvency test. This is based on reasons to prevent debtors whose assets are more than their debts being declared bankrupt by the court.